Brand Image Tri Rismaharini dalam Pilkada Serentak 2015 di Media Jawa Pos Edisi Oktober – Desember 2015 (Jurnal Kajian Media, 2017)
The image is a crucial thing for a victory to compete for the people's sympathy in the election to the Region. Therefore, every candidate head of the region should be able to image himself through his campaign strategy positively. The campaign teams of each candidate's head will try to create a positive self-image of the candidate pair in the eyes of the community because positive self-image and achievement of the candidate of the head of a region have big influence for the novice voters in making their choice. The figure of Tri Rismaharini becomes interesting to be discussed in the research because Risma became the first woman to be elected directly to the mayor through the election of regional heads throughout the history of Indonesian democracy in the reform era and was the first female chairman of the region in Indonesia who repeatedly included in the list of world's best leaders Tri Rismaharini . The purpose of this research is to know the brand image Tri Rismaharini in Pilkada simultaneously in 2015 in Jawa Pos edition of October - December 2015. The approach of this research is descriptive qualitative which gives in-depth and detailed understanding related to a social event or phenomenon.The unit analysis in research These are all the news elements of a news text, namely: title, news lead, body/news content, cover, and photo/graphics. The results of this study show that the Java Pos media edition of October - December 2015 depict image of Tri Rismaharini as a simple and honest figure, a figure who has a high social awareness, a controversy figure associated with the case of Pasar Turi Baru, Arek Suroboyo figure who Will be the winner in Surabaya Mayor election 2015-2020 period. Keywords: Brand image, Mayor election, media